Pengaruh Sikap terhadap Lingkungan (Environmental Attitude) dan Kepribadian (Big-Five Personality) terhadap Intensi untuk Bertindak (Intention to Act) Siswa - Dewi Larasati; I Made Putrawan; Diana Vivanti Sigit (IJEEM - Indonesian Journal of Environmental Education and Management, 2020)
Global warming is one of the major challenge to humankind because this kind of environmental issue is a global issue which not only faced by one country but the whole world. The main cause of global warming is human activity. Human have to change their behavior in order to protect the environment especially the student because they’re the living next generation. Behavior often occur because there is intention to do so. One’s desire to act appears to be affected by a host of personality factors including environmental attitude. This study aimed to determine the effect of environmental attitude and personality on the intention to act that students have. Research conducted at SMAN 29 Jakarta on the Semester I of 2019/2020 school year. The method used is the survey with quantitative-causal causal approach and path analysis. The sample were 93 students of class X MIPA. There were three instrument used for measuring environmental attitude, personality, and intention to act with reliability of 0.774, 0.786, and 0.84. Based on hypothesis test, it suggested that there was indirect effect between environmental attitude and intention to act via personality.As the results, it can be concluded that personality is suitable as a mediator of variables between environmental attitude and personality. Keywords: Student, environmental attitude, personality, intention to act, path analysis.